PENGOLAHAN LIMBAH LABORATORIUM KIMIA DENGAN KOMBINASI METODE ELEKTROKOAGULASI, FILTRASI DAN PENGIKATAN LOGAM DENGAN ASAM JAWA - Fadhila, Rahayu Yuliastri; Ihsan, Ihsan; Sahara, Sahara (Universitas Islam Negeri Alauddin Makassar, 2018)
The research aimed to identify the early characteristics of the chemical waste and characteristic of chemical waste laboratory after mixed and combination with electrocoagulation method, filtration, and tying for metal and tamarin. Waste that processed are the residu waste from AAS testing in chemical instrumentation laboratory, Chemistry Department of UIN Alauddin Makassar. The research results obtained AAS waste before processed having the characteristics on pH parameters are 0.56, COD are 195000 ppm, Mercury (Hg) are 15 ppm, Cadmium (Cd) are 2.79 ppm, Lead (Pb) are 3.49 ppm, and cloudiness of 192 FTU. While AAS waste after mixed and combination with electrocoagulation method, filtration, and and tying for metal and tamarin having the characteristics of pH parameter are 2.76, COD are 20000 ppm, Hg are 0.001 ppm, Cd are 0.002 ppm, Pb are 0.123 ppm, and cloudiness of 662 FTU.Â